Atlantic salmon living on the edge: Smolt behaviour and survival during seaward migration in River Minho. Issue 1 (2nd August 2020) - Flávio, Hugo; Caballero, Pablo; Jepsen, Niels; Aarestrup, Kim
Abstract: The Atlantic salmon ( Salmo salar ) population of the River Minho represents the southern natural distribution edge of the species. In line with the general trend for Atlantic salmon, this population has been declining over the years and is now at a critically low level. With river connectivity compromised by a large dam just 80 km upstream the River Minho's outlet, and an expected deterioration of climatic conditions, it is urgent to increase our knowledge of this population and identify survival bottlenecks that can be addressed. In this study, we used radio and acoustic telemetry to track Atlantic salmon smolts during their migration towards the sea and record both survival rates and possible causes of mortality. The recorded survival for the tagged migrating Atlantic salmon remained below 55% in the three studied years, indicating that the in‐river loss of smolts is likely a strong constraint to this population. From the smolts to which a likely cause of mortality could be attributed (34%), most appear to have been removed from the river (25%), with two confirmed events of bird predation and one of mammal predation. Interestingly, eight tags were recorded moving back upstream, likely indicating predation by larger fish. Increasing predator populations (e.g. cormorants, Phalacrocorax carbo ) and invasive predators (e.g. American mink, Neovison vison ) lead to elevated predation pressure on this already strained Atlantic salmon population, and further studies quantifying their impact in more detail could prove crucial for future management considerations.